The Cope Rearrangement - a Reaction with a Manifold Mechanism? - Rudolf Wehrli; Daniel Belluš; Hans-Jürgen Hansen; Hans Schmid (CHIMIA)
For the Cope rearrangement of hexa-1,5-dienes (cf. 1) to isomeric forms (cf. 1'), more mechanisms are at one’s disposal than was hitherto accepted. Depending on the choise of the structure, the kind of substituents of the Cope system or on the reaction conditions, most of the thinkable mechanisms can be defined. Twostep Cope processes are characterized by dissociation and recombination or by the intervention of diradicals or zwitterions as intermediates. Concerted processes can occur via the “classical” pericyclic (aromatic) or via a diradicaloid transition state. Whereas the unsubstituted hexa-1,5-diene and its derivatives with conjugative substituents in positions 1,3,4 or 6 follow the pericyclic route, systems with radical stabilizing substituents in positions 2,5 prefer to react via the diradicaloid pathway. Thus, hexa-1,5-dienes represent, from a mechanistical standpoint, quite ductile systems.